DAMPAK PENGGUNAAN SMARTPHONE TERHADAP SOSIAL EMOSIONAL ANAK USIA 4-5 TAHUN DI RA FATHURROZAK SIHITANG PADANGSIDIMPUAN - Susilawati Munthe; Lis Yulianti Syafrida Siregar; Sakinah Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the impact of smartphone use on the social emotional of children aged 4-5 years at RA Fathurrozak Sihitang Padangsidimpuan. This study specifically focuses on children aged 4-5 years at RA Fathurrozak Sihitang Padangsidimpuan. The formulation of the problem in this study is how the impact of smartphone use on the social emotional of children aged 4-5 years at RA Fathurrozak Sihitang Padangsidimpuan. The main objective of this study is to find the impact of smartphone use on the social emotional of children aged 4-5 years at the school. This study uses a qualitative descriptive research method, using observation, interviews, and documentation for data collection. The subjects of this study included four children aged 4-5 years and their parents, as well as teachers at RA Fathurrozak Sihitang. The results of the study show that: the impact of smartphone use on the social emotional of children aged 4-5 years at RA Fathurrozak Sihitang Sidimpuan has a significant influence, namely there are negative and positive influences. Where children still often show less interaction with peers and the surrounding environment and difficulty managing emotions. In this case, children also experience increased knowledge through the educational content they view. Researchers stated this based on interviews and observations at the study site. Of the four children, three had poor social-emotional skills because, after using smartphones, they became more withdrawn and unwilling to go out. This occurred because parents did not limit smartphone usage time, leading the children to be more interested in playing with their phones than playing outside. Meanwhile, one child had good social-emotional skills, considered good because the child's social-emotional development met the following indicators: cooperation, willingness to share, two-way communication, and emotional management, including empathy and the ability to play with peers.